Water jet: a simple method for classical conditioning in fish - Barretto, Adriana Beatriz [UNESP]; Maia, Caroline Marques [UNESP]; Alves, Nina Pacheco Capelini [UNESP]; Giaquinto, Percilia Cardoso [UNESP] (Springer Nature, 2018)
Classical conditioning in animals is a learning procedure involving a biologically relevant stimulus paired with a previously neutral stimulus. In fish, light and sound are frequently used as previously neutral stimuli for conditioning tests. However, in laboratory experiments with replicates, such stimuli may influence the responses of fish in nearby aquariums. Herein, we developed a simple applicable methodology for classical conditioning in fish that prevents this type of influence. We isolated fish in individual aquariums and introduced a water jet that caused localized water movement, followed by the introduction of a food pellet. These procedures were repeated for each fish for 20 days. After 14 days, all fish were conditioned. Moreover, in subsequent probe trials (memory retention tests) conducted within 32 days after conditioning procedures, fish responded accordingly. These findings corroborate the applicability and usefulness of the method tested herein especially under lab conditions. Therefore, we suggest that a simple water jet is a useful and reliable tool for fish conditioning in future studies.
Keywords: Classical conditioning; Fish learning; Memory; Water jet